ANALYSIS OF PERFORMANCE ASSESSMENT, PROFESSIONALISM AND SKILLS ON THE PERFORMANCE OF MSME EMPLOYEES - Sinta Petri; Andi Tri Haryono; Aziza Restu Febrianto (Sean Institute, 2023)
This study aims to examine Job Assessment, Professionalism and Skills on Employee Performance. This research was conducted at SMEs. The population of this study were employees of the weaving department at SMEs. The sampling method used purposive sampling by distributing questionnaires to employees in the weaving department and conducting interviews. The data analysis technique used is multiple linear regression analysis.The results showed that Job and Skills Assessment had a significant positive effect on Employee Performance. Professionalism has no significant positive effect on employee performance. Job Assessment, Professionalism and Skills have a positive effect simultaneously on Employee Performance.